Study of semicircular sections through CFD software for rainwater retention in arid areas - Janampa Guardia, Jonathan Isai; Jacinto Ferrer, Humberto Javier; Carmona Arteaga, Abel (LACCEI, 2024)
The study focuses on the evaluation of water retention through the use of semicircular sections. It uses an experimental approach to analyze how semicircular sections in plant environments and where the population are located in order to retain water flow and improve soil moisture. The research involves measuring the kinetic energy of water after passing through these curved sections to determine how they affect fluid retention. The results help to understand how the design of curved sections effectively benefits to control water pressure and may have applications in water resources management and civil engineering to prevent erosion and ensure a controlled and safe flow for inhabitants and the community. vegetation.